Adsorption isotherms of hydrogen: The role of thermal fluctuations - Mecke, Klaus; et al. (Physical Review Letters, 2001)
It is shown that experimentally obtained isotherms of adsorption on solid substrates may be completely reconciled with Lifshitz theory when thermal fluctuations of the free film surface are taken into account. This is demonstrated for hydrogen adsorbed on gold as a model system. Analysis of the fluctuation contributions allows one to determine the surface tension of the free hydrogen film as a function of film thickness. It is found to decrease sharply for film thicknesses below seven atomic layers.